Development of resilience concept in scientific literature of recent years - Assonov, Дмитро; Khaustova, Олена (Psychosomatic Medicine and General Practice, 2019)
Background. Increasing number of resilience studies in recent years is accompanied by a reconsideration of its concept. Researchers note that there is exist a problem of unified understanding of resilience. There has been a number of English studies with a fundamental analysis of accumulated definitions and conceptual problems of resilience, but an analysis of accumulated in recent years Ukrainian literature related to resilience has not yet been done. A clear terminological definition of resilience and a distinction with closely related concepts becomes a necessary prerequisite for further research on its reliable evaluation and development of new approaches to therapy. Aim. To systematize and compare the approaches presented in the Ukrainian and foreign scientific literature in recent years to conceptualize resilience and its distinction with other terms, and to offer recommendations for further resilience research. Materials and methods. A qualitative and quantitative content-analysis of scientific Ukrainian and English literature, published from 2016 to December 15, 2019, outlining various approaches to interpreting the concept of resilience, was conducted. Results and discussion. There are both divergent and common points in conceptualization of resilience presented in Ukrainian-language literature and the latest global conceptualization trends. In English literature, as well as in Ukrainian, resilience belongs to the category of adaptation, is preceded by a traumatic event or stressful impact, and defined as a dynamic process. At the same time, in Ukrainian literature, the trajectory of resilience is interpreted mainly as resistance to stress, maintaining of normal functioning in conditions of traumatic impact, while in the English literature conceptualization of resilience as a return to the previous level of functioning is predominated. Conclusions. Based on the analysis and synthesis of information, we propose to define resilience as an adaptive dynamic process of returning to initial psychosocial functioning after a period of maladaptive functioning due to the disorganizing effect of psycho-traumatic factors. We recommend to clearly differentiate resilience with stress-resistance, hardiness, coping, and post-traumatic growth, and not use these terms as synonyms for resilience, for accurate operationalization and avoidance of terminological confusion.